Rhetoric Structure of the Master of Ceremony and the Function of the Akikah Event in Lubuklinggau City - Noermanzah Noermanzah; Syafryadin Syafryadin; Ocva Widya Castrena; Syaiful Abid (Universitas Bengkulu, 2020)
This study aims to describe the rhetorical structure of the master of ceremonies and the function of Akikah for the community in Akikah events in the Lubuklinggau City. The research method used is a qualitative method. Data collection techniques using the technique of record, see, and proficient. Data analysis techniques with steps to transcribe data, data reduction, data presentation, interpretation, and conclusions. Test the validity of the data by member checking and expert validation test. The results showed that the rhetoric structure of the master of ceremonies in the Akikah ceremony in Lubuklinggau City consisted of: 1) opening the Akikah ceremony, including opening greetings, thanksgiving to God, reciting basmallah, and conveying the purpose of the event, 2) The contents of the Akikah ceremony, including: delivery of the composition of the arrangement Akikah program, introduction to the next program (transition) by inviting the reading of the Koran, introduction to the reading of the Koran, introduction to the next program (transition) section to deliver a speech, the host commenting on the delivery of greetings, introduction to the next event (transition) part of the reading of Al-Barzanzi, introduction to the next event (transition) section of baby hair shaving, and the host's commentary on baby hair shaving, and 3) closing of the Akikah event includes the introduction of the next program section (transition) of prayer reading, carrier comments the event took the form of an apology, and closing greetings. Then, akikah has a function for the people of Lubuklinggau City, namely as a media to announce news of the birth of a baby, as a form of gratitude to Allah, cultivate faith, implement Islamic law, can provide intercession for both parents, and make a child who is pious or saleha.